The Nyström Method for Elastic Wave Scattering by Unbounded Rough Surfaces (Journal of Computational Mathematics, 2024)
We consider a numerical algorithm for the two-dimensional time-harmonic elastic wavescattering by unbounded rough surfaces with Dirichlet boundary condition. A Nyströmmethod is proposed for the scattering problem based on the integral equation method.Convergence of the Nyström method is established with convergence rate depending onthe smoothness of the rough surfaces. In doing so, a crucial role is played by analyzingthe singularities of the kernels of the relevant boundary integral operators. Numericalexperiments are presented to demonstrate the effectiveness of the method.
Keywords: Elastic wave scattering; Unbounded rough surface; Nyström method.